Nonlinear optical characteristics of monolayer MoSe2. Issue 7 (1st April 2016) - Le, Chinh Tam; Clark, Daniel J.; Ullah, Farman; Senthilkumar, Velusamy; Jang, Joon I.; Sim, Yumin; Seong, Maeng‐Je; Chung, Koo‐Hyun; Park, Hyoyeol; Kim, Yong Soo
Abstract : A high second‐order susceptibility and strong laser‐induced damage threshold of two‐step grown MoSe2 monolayer is reported. This superior nonlinear optical behavior is attributed to its electronic band structure modification when transition metal dichalcogenides (MX2 ) are thinned down to the monolayer regime. Futher, wavelength‐dependent second harmonic scan can identify the bound excitonic states much more efficiently, compared with the PL method at room temperature. Abstract : In this study, we utilized picosecond pulses from an Nd:YAG laser to investigate the nonlinear optical characteristics of monolayer MoSe2 . Two‐step growth involving the selenization of pulsed‐laser‐deposited MoO3 film was employed to yield the MoSe2 monolayer on a SiO2 /Si substrate. Raman scattering, photoluminescence (PL) spectroscopy, and atomic force microscopy verified the high optical quality of the monolayer. The second‐order susceptibility χ (2) was calculated to be ∼50 pm V −1 at the second harmonic wavelength λ S H G ∼810 nm, which is near the optical gap of the monolayer. Interestingly, our wavelength‐dependent second harmonic scan can identify the bound excitonic states including negatively charged excitons much more efficiently, compared with the PL method at room temperature. Additionally, the MoSe2 monolayer exhibits a strong laser‐induced damage threshold ∼16 GW cm −2 under picosecond‐pulse excitation. Our findings suggest that monolayer MoSe2 can be considered as a promising candidate for high‐power, thin‐film‐based nonlinear optical devices and applications.